1996
DOI: 10.1128/aac.40.6.1352
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical effect of clindamycin in experimental, acute toxoplasmosis in cats

Abstract: Cats were experimentally inoculated parenterally with the ME49 strain of Toxoplasma gondii to characterize the efficacies of two different dosages of orally administered clindamycin hydrochloride in the treatment of ocular toxoplasmosis. Concentrations of clindamycin hydrochloride at levels previously suggested to be inhibitory to T. gondii replication in vitro were achieved in the serum and aqueous humor but not in the cerebrospinal fluid. Antibiotic therapy, initiated 7 days after inoculation, resulted in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…This effect was responsible for the severe intraocular presentation of the disease compared with the control group [369].…”
Section: Macrolidesmentioning
confidence: 92%
See 1 more Smart Citation
“…This effect was responsible for the severe intraocular presentation of the disease compared with the control group [369].…”
Section: Macrolidesmentioning
confidence: 92%
“…Recurrence was prominent after transplant surgery [400,401]. Recurrence was most probably due to rupture of the cysts and dissemination of infection [369]. Other studies showed that their combined use was not associated with any adverse effect, nor was it associated with delay in onset of inacitivity [402][403][404][405], except in very selective severely inflamed eyes, in which corticosteroid use resulted in a poor outcome [404][405][406][407].…”
Section: Role Of Corticosteroid Administrationmentioning
confidence: 99%
“…Twelve cats were inoculated intrapressed at a constant rate in cells, to control for sample-to-sample venously with 5 1 10 6 TCID 50 of cell-free virus culture supernatant variation in efficiency of mRNA isolation. as described by Davidson et al [27]. The remaining 10 cats were…”
Section: Methodsmentioning
confidence: 99%
“…The NCSU 1 strain of FIV was originally is different than the length of the cDNA products [33]. The competisolated from a naturally infected cat at the North Carolina State itive fragment also contains primer sites for glyceraldehyde-3-University College of Veterinary Medicine and has been described phosphate dehydrogenase (G3PDH), a housekeeping gene exin detail elsewhere [18,27,30]. Twelve cats were inoculated intrapressed at a constant rate in cells, to control for sample-to-sample venously with 5 1 10 6 TCID 50 of cell-free virus culture supernatant variation in efficiency of mRNA isolation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation